Pengaruh Latar terhadap Karakter Utama (Lelaki Tua) dalam Cerpen "Sepotong Tangan" Oleh Ratih Kumala - Untung (DIALEKTIKA: Jurnal Ilmiah Pendidikan Bahasa, Sastra, dan Matematika, 2015)
The purpose of this study were to reveal kinds of setting form in the short story “Sepotong Tangan” by Ratih Kumala and whether they influence the main (lelaki tua) in the short story ‘Sepotong Tangan” by Ratih Kumala? This study used a qualitative approach to the intrinsic elements of literary works, by utilizing the concept of the main character and setting to reveal and decipher focus of research in the short stories. Data collection techniques used in this study was a literature review technique. The research data is a word, phrase, sentence, and dialogue, which is associated with a research focus in the short story “Sepotong Tangan” by Ratih Kumala published by Gramedia Pustaka Utama, 2008. The procedures used in data collection were as follows; read the short story “Sepotong Tangan” by Ratih Kumala, underlining phrases, sentences, paragraphs, and the dialogue relating to the focus of research, quoting, and identifying and selecting and classifying the data according to its category of research. Analysis technic was performed as follows; classifying kind of setting form, and its influence on the main character, define and describe, interpret, and make conclusions. In line with the purpose of research, the results of this study revealed that the study of the short story “Sepotong Tangan” by Ratih Kumala show, setting influenced the development of the main character of (lelaki tua). The Dominant settings in this story is physical settings, such as setting the time and place. Because of the dominance of the settings, it can also be called a typical setting for the protrusion of certain setting a story. There is an only spiritual setting as it relates to the procedures or customs handling the dead bodies in Indonesia, whereas a neutral setting cannot be found in this story.